DEPOSIT INSURANCE IN THE PERUVIAN FINANCIAL SYSTEM - Rodríguez Cairo, Vladimir (2015)
This study explains the importance of creating deposit insurance in the financial system to prevent massive withdrawals of bank capital; and on that basis, seeks to answer the question: Why is it important for the financial system to have coverage for saving deposits through insurance?In that regard, it should be noted that the nature of the study is explanatory type and the research methods used are analytic and inductive. Furthermore, we used secondary information sources and the technique used was documentary examination. From this perspective, for a better understanding of the proposed theme, content is structured in three parts: The first includes the microeconomic foundations of deposit insurance in the financial system, the second states the importance and protection of savings and the third covers the Deposit Insurance Fund in Peru. Finally, conclusions are presented and the references are disclosed.